Analysis of Cultural Values In Educational Leadership Styles In Indonesia: Perspektives of Tradision and Modernity - Rahmadini, Sintia Dwi; Khaerani, Aurelia; Ainiyah, Thohirotul; Khozin, Mochammad (JIEM (Journal of Islamic Education Management), 2024)
This research analyzes cultural values in educational leadership styles in Indonesia from the perspective of tradition and modernity. In diverse social and cultural contexts, leadership styles in educational institutions in Indonesia are often influenced by traditional values such as mutual cooperation, deliberation, and mutual respect and appreciation. On the other hand, modernity brings an approach that prioritizes efficiency, innovation and flexibility. This study uses library research methods to analyze cultural values in leadership styles applied in educational institutions. The research results show that leaders who are able to integrate local cultural values with modern leadership practices can create leadership models that are relevant to Indonesia's socio-cultural conditions and support continuous improvement in the quality of education. By understanding the dynamics between tradition and modernity, it is hoped that this research will be able to provide a valuable perspective to support the development of leadership that is inclusive and adaptive to the dynamics of changing times. Thus, this research not only contributes to leadership theory, but also provides practical recommendations for educational leaders in managing their institutions effectively and sustainably.Keywords: Cultural Values, Education Leadership Styles, Tradision, Modernity.Penelitian ini menganalisis nilai budaya dalam gaya kepemimpinan pendidikan di Indonesia dengan perspektif tradisi dan modernitas. Dalam konteks sosial dan budaya yang beragam, gaya kepemimpinan dalam lembaga pendidikan di Indonesia sering kali dipengaruhi oleh nilai-nilai tradisional seperti gotong royong, musyawarah, serta sikap saling menghormati dan menghargai. Di sisi lain, modernitas membawa pendekatan yang lebih mengutamakan efisiensi, inovasi, dan keanehan. Studi ini menggunakan metode penelitian kepustakaan (penelitian perpustakaan) untuk menganalisis nilai budaya dalam gaya kepemimpinan yang diterapkan di lembaga pendidikan. Hasil penelitian menunjukkan bahwa pemimpin yang mampu mengintegrasikan nilai-nilai budaya lokal dengan praktik kepemimpinan modern dapat menciptakan model kepemimpinan yang relevan dengan kondisi sosial-budaya Indonesia dan mendukung peningkatan kualitas pendidikan secara berkelanjutan. Melalui pemahaman terhadap dinamika antara tradisi dan modernitas, penelitian ini diharapkan mampu memberikan perspektif yang berharga untuk mendukung pengembangan kepemimpinan yang inklusif serta adaptif terhadap dinamika perubahan zaman. Oleh karena itu, penelitian ini tidak hanya memberikan kontribusi pada teori kepemimpinan, tetapi juga memberikan rekomendasi praktis bagi para pemimpin pendidikan dalam mengelola lembaga mereka secara efektif dan berkelanjutan.Kata kunci: Nilai Budaya, Gaya Kepemimpinan Pendidikan, Tradisi, Modernitas.